Strategi Pengembangan Industri Kecil Menengah Melalui Bantuan Dinas Perikanan dan Kelautan: Studi Kasus Kelompok Olah Pasar Doa Ibu Desa Jaya Mukti Kecamatan Banyusari Kabupaten Karawang - Devi Puspita Sari; Enjang Suherman; Laras Ratu Khalida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Kelompok olah pasar doa ibu has been around since 1990, founded and chaired by Mr. Kaning. The existing products are marine products. The market sports group has 10 members and has not experienced any changes since its inception until now. The problems that occurred in the Mother's Prayer Market Processing Group were the management of assistance from the fisheries and maritime department, hampered capital circulation, and human resources experiencing problems. This research aims to find out strategies for the development of small and medium industries in the mother's prayer market group. This research method uses the SWOT analysis method to assist research analysis in determining quadrant positions and alternative strategies to be used. The research results obtained are that the market processing group is in quadrant III position with a difference between IFAS, namely -0.24 and the difference between EFAS, namely 0.64. With these results, there is a big opportunity but it has internal weaknesses, so the alternative used is the WO strategy. To minimize internal weaknesses, strategies such as training and coaching are needed for human resources in the market processing group. By implementing this strategy, it is hoped that the market transformation team will gain human capital development and have an impact on the growth of the company they lead.